A New High-performance Liquid Chromatography Method Development for Cleaning Validation of Adapalene Active Pharma Ingredient - Prashanthi, Dr. Y. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The analytical method has been developed to evaluate the efficacy of the cleaning procedure of all the equipment involved in the production of final active ingredients. The choice of the methodology is based on the production method and on the intrinsic properties of the products. For this validation, high-performance liquid chromatography (HPLC) method has been chosen. Materials and Methods: The HPLC chromatographic separations were achieved on (100 mm Ã— 4.6 mm), 3.5 Î¼m make: Phenomenex column employing acetonitrile and 0.5% orthophosphoric acid aqueous solution in the ratio of 35:65 as mobile phase with flow rate 1.0 mL/min was chosen. The column temperature was maintained at 30Â°C, and a detector wavelength of 230 nm was employed. Results and Discussion: The method was successfully validated by establishing system suitability, specificity, linearity, accuracy, limit of detection (LOD), and limit of quantification (LOQ) as per ICH guidelines. Conclusion: The method was completely validated showing satisfactory data for all methods - validated parameters tested. Satisfactory validation parameters such as linearity, recovery, precision, LOD, and LOQ were established by following ICH guidelines. Therefore, the proposed analytical procedure could be useful for regular monitoring, pharma manufacturing laboratories, and researchers.